Stent restenosis: identifying predictors. (3rd May 2023) - Paralta De Figueiredo, M; Carias, M; Picarra, B; Rocha De Almeida, A; Claudio, F; Rocha, R; Trinca, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Despite advancements in stent technology, such as the appearance of the drug-eluting stents, stent restenosis remains a common post-procedure complication and is associated with a higher morbimortality. These patients frequently need repeat revascularisation and pose a therapeutic challenge. Purpose: This study aims to characterize if it is possible to identify clinical predictors of stent restenosis. Methods: We retrospectively observed a population of 9815 patients (D) admitted with acute coronary syndrome (ACS) and divided them into two groups: those who had stent restenosis (D1), and those who did not (D2). We then compared both groups regarding age, sex, personal history of smoking (both current or former smokers), hypertension, dyslipidaemia, diabetes mellitus, stroke/TIA, chronic kidney disease and stent location. Results: D1 consisted of 2, 9% of the population. Both groups had similar age (D1: 67, 95±10, 35 years vs. D2: 68, 56±11, 57years) and were predominantly of the male sex (75, 9% vs. 73, 3%). D1 had a significantly higher prevalence of diabetes (3, 1% vs 2, 7%, p=0, 008; odds ratio: 1, 183, 95% CI [1, 044;1, 340]); dyslipidaemia (72, 4% vs 59, 0%, p<0, 001; odds ratio: 1, 821, 95% CI [1, 586;2, 092]); hypertension (86, 4% vs 80, 8%, p<0, 001; odds ratio: 1, 507, 95% CI [1, 259;1, 805]); smoking (38, 1% vs 33, 6%, p=0, 003; odds ratio: 1, 215, 95% CI [1, 069;1, 381]); and chronic kidney disease (12, 1% vs 10, 0%, p=0, 003; odds ratio 1, 235, 95% CI [1, 020;1, 495]) than D2. When comparing stent location, restenosis was more frequently observed in the right coronary artery (4, 5% vs 2, 3%, p<0, 001; odds ratio 2, 016, 95% CI [1, 775;2, 289]), with no significant differences in relation to other segments. There were no statistically relevant differences regarding stroke/TIA between the groups. Conclusions: In patients with ACS, stent restenosis seems to be associated with a significantly higher prevalence of diabetes, hypertension, dyslipidaemia, history of smoking and chronic kidney disease. Right coronary artery stenting also seems to be associated with a higher rate if restenosis when compared to other revascularised segments. These characteristics could help predict which patients are at a higher risk and need closer monitoring, potentially improving outcomes. Further developing a score with these predictors could be of interest.